Sweat water biological épuration by phytophagous and plancton eating fishes (Ctenopharyngodon ideila (vail and Hypophthalmichthys Molitrix Ivall): - ΦΩΤΗΣ, Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this study the biological way to be exempt of phytoplancton and water weeds by means of phytopagous and plancton eating fishes Ctenopharyngodon ideila and Hypophtalmichtys Molitrix. This way of facing is more efficient from all the others because it is not causing problems in the environment and a better exploitation of the water is being done. The possibility of its application depends on two factors. a) From the water temperature and β) From the water system. The water temperature in the longest period of the year must be above 12°C for phytophagous fishes and above 6°C for plancton eating fishes. The water system must be close because the phytophagous fishes have the tendency of immipration. The abovementioned fishes not only free the water from non desirable vegetation but at the same time give us meat of excellent quality.